Associations Between Enteral Nutrition and Acute Respiratory Infection Among Patients in New York Metropolitan Region Pediatric Long‐Term Care Facilities. (15th February 2018) - Burgermaster, Marissa; Murray, Meghan; Saiman, Lisa; Seres, David S.; Larson, Elaine L.
Abstract: Background: Pediatric long‐term care facilities (pLTCF) serve a complicated and resource‐intensive patient population with high usage of nutrition support. However, the relationship between nutrition support and outcomes among pLTCF residents is not well understood. We described this relationship in three metropolitan New York pLTCF and a subsample of infants from one of these facilities with a feeding disorders unit. Methods: In this prospective cohort study, we used logistic regression to assess relationships between enteral nutrition (EN), and acute respiratory infections (ARI) among residents (n = 720, 50% male, mean age = 5.5 years, mean number comorbidities = 2.1) and infant subsample (<1 year, n = 208, 50% male, mean number comorbidities = 2.0). We tested these associations in multivariable models controlling for numbers of comorbidities and infections. Results: Many residents received nutrition via percutaneous (59%) or nasogastric (15%) feeding tubes. In univariate analyses, residents receiving EN had more comorbidities. In multivariable analyses, EN was associated with ARI (incidence rate ratio = 1.65, p < .001). Among infants in the specialized unit, greater risk of ARI was associated only with percutaneous (incidence rate ratio = 1.94, p < .01) feeding. EN was associated with lower odds of being discharged home (OR = 0.45, p < .01). Conclusion: The prevalence of EN, complexity of cases, and necessity of long‐term EN make nutrition support important in pLTCFs. Differences in EN types and adverse outcomes in the infant subsample suggest different care is necessary for this subpopulation. Results provide context for improving quality of care and clinician/caregiver education for this population.